Sperm capacitation in humans is transient and correlates with chemotactic responsiveness to follicular factors. - Cohen-Dayag, A (1995)
In humans, only a small fraction (2-12%) of a sperm population can respond by chemoattraction to follicular factors. This recent finding led to the hypothesis that chemotaxis provides a mechanism for selective recruitment of functionally mature spermatozoa (i.e., of capacitated spermatozoa, which possess the potential to undergo the acrosome reaction and fertilize the egg). This study aimed to examine this possibility. Capacitated spermatozoa were identified by their ability to undergo the acrosome reaction upon stimulation with phorbol 12-myristate 13-acetate. Under capacitating conditions, only a small portion (2-14%) of the spermatozoa were found to be capacitated. The spermatozoa were then separated according to their chemotactic activity, which resulted in a subpopulation enriched with chemotactically responsive spermatozoa and a subpopulation depleted of such spermatozoa. The level of capacitated spermatozoa in the former was approximately 13-fold higher than that in the latter. The capacitated state was temporary (50 min < life span < 240 min), and it was synchronous with the chemotactic activity. A continuous process of replacement of capacitated/chemotactic spermatozoa within a sperm population was observed. Spermatozoa that had stopped being capacitated did not become capacitated again, which indicates that the capacitated state is acquired only once in a sperm's lifetime. A total sperm population depleted of capacitated spermatozoa stopped being chemotactic. When capacitated spermatozoa reappeared, chemotactic activity was restored. These observations suggest that spermatozoa acquire their chemotactic responsiveness as part of the capacitation process and lose this responsiveness when the capacitated state is terminated. We suggest that the role of sperm chemotaxis in sperm-egg interaction in vivo may indeed be selective recruitment of capacitated spermatozoa for fertilizing the egg.